Developing multichannel surface EMG acquisition system by using instrument opamp INA2141 - Ghapanchizadeh, Hossein; Ahmad, Siti Anom; Ishak, Asnor Juraiza (IEEE (IEEE Xplore), 2014)
Electromyography (EMG) is a signal which produces from motor units (MUs) in the muscles during contraction activities. By detecting EMG, it can show muscle contractions and body members' movement such as hand, eyes and legs. Monitoring and analyzing these signals from the skin which called Surface EMG (SEMG) required some essential components, for example electrode, data acquisition (DAQ) system and analog to digital converter (ADC). This paper presents a suitable and a portable DAQ system for collecting data from SEMG electrodes by using INA2141 IC. Furthermore, presented DAQ system is able to change the differential channel numbers according to different studies. The proposed system is developed with lower cost, where the components used common parts and are easily obtained. Moreover, by expending number of channels the presented circuit has suitable for wide range of research in SEMG area. In addition, users can use any type of connection for electrodes. Therefore, users can use any SEMG electrode types.